EVALUASI PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PERUSAHAAN KONSTRUKSI - Ira Riswana; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Occupational safety and health is important not only in companies but everywhere, such as educational institutions, construction sector and companies. This obligation regarding the implementation of the K3 Management System by each company is regulated in PP No. 50 of 2012 concerning the Implementation of the Occupational Health and Safety Management System. This research is a literature review, where the data sources in this study come from several published journals obtained from the search engine "google scholar". The purpose of this study is to determine the evaluation of the implementation of the K3 management system in construction companies. The implementation of the Occupational Safety and Health Management System (SMK3) has been going well and in accordance with Government Regulation No. 50 of 2012. However, there are still some obstacles found such as lack of cooperation between employees/staff, lack of worker awareness of the use of PPE. It is hoped that the company can continue to maintain policies and implement plans in order to create a safe and comfortable work area for workers